TRAINING, ENVIRONMENT, AND EMPLOYEE PERFORMANCE : SYSTEMATIC LITERATURE REVIEW - Rosa Indah Parawansah; Sopiah Sopiah; Syihabudhin Syihabudhin (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This article aims to analyze training, work environment, and employee performance. This article was prepared using the Systematic Literature Review (SLR) method. SLR is a systematic literature review method that identifies, reviews, evaluates, and interprets all available research. With this method, researchers review and identify journals in a structure that, in each process, follows predetermined steps. Employee performance is one of the main factors for the company to achieve its goals. Apart from being a factor in achieving goals, employee performance is also a way to measure the quality of human resources in a company. The analysis of various journals indicates that both training and the work environment significantly influence employee performance. The training given to employees will improve their performance, and a comfortable work environment will also improve employee performance. Keywords: Training; Environment; Employee Performance